Análise multivariada entre medidas in vivo, na carcaça e na carne de cabritos do Alto Camaquã - Oliveira, Róberson Macedo de (2012)
The relationship between in vivo characteristics, carcass and meat goats from the region of Camaquã, were evaluated from the analysis of multivariate data. Data from 14 castrated males, born March-April/2009 and sacrificed with 8-9 months of age, originating from the familiar raising unit Casa de Pedra, RS, Brazil (Lot a) for 20 castrated male goats, born in June-July/2008, slaughtered at 11-12 months of age, originating from the familiar raising unit Arroio da Palma, RS, Brazil (Lot b), underwent randomization test and principal component analysis. The test result randomization between lots accepted that the set of variables Lots differ. The principal component analysis using forty-five descriptor variables showed that about 37.75% of the total variation is explained by the first component and 20.83% for the second. When using the 24 descriptors with the highest correlation with the ordination axes observed significant correlations for most variables. The principal component analysis explained more than 75% in the first two components. The characteristics that best explained the object of the study were: chilled carcass weight, hardness, right carcass, chewiness, hot carcass weight, global evaluation, live weight, yield hot carcass. The ordination diagram synthesized information and descriptive variables. The use of multivariate techniques may be recommended to evaluate the goat meat.